Ordinary Genomes : Science, Citizenship, and Genetic Identities - Taussig, Karen-Sue, 1962- (Book collections on Project MUSE., 2009)
Explores the mutually constructive relationship between increasing scientific knowledge of human genetics and cultural identity through a case study of the development and reception of genomics in the Netherlands.